Suitability of superficial electron paramagnetic resonance dosimetry for in vivo measurement and verification of cumulative total doses during IMRT: a proof of principle - Höfel, Sebastian; Fix, Michael K.; Drescher, Malte; Zwicker, Felix (Zeitschrift für medizinische Physik, 2021)
Purpose - The present study investigates superficial in vivo dosimetry (IVD) by means of a previously proposed electron paramagnetic resonance (EPR) dosimetry system aiming at measuring and verifying total doses delivered by complex radiotherapy treatments. In view of novel regulatory requirements in Germany, differences between measured and planned total doses to the EPR dosimeters are analyzed and compared to reporting thresholds for significant occurrences. - Methods - EPR dosimeters, each consisting of one lithium formate monohydrate (LFM) and one polycrystalline l-alanine (ALA) pellet, were attached to the surface of an anthropomorphic head phantom. Three head and neck treatments with total target doses ranging from 30 to 64Gy were fully delivered to the phantom by helical tomotherapy. During each treatment, eight EPR dosimeters were placed at distinct spots: (i) within or next to the planning target volume (PTV), (ii) near to organs at risk including the parotids and the lenses, (iii) at the thyroid lying out-of-field. EPR read out was always performed after all fractions were delivered. EPR results were compared to thermoluminescence dosimeter (TLD) measurements and to the planned total doses derived from the treatment planning system (TPS). Planned total doses to the EPR dosimeters ranged from about 2 to 64Gy. - Results - By taking uncertainties into account, the measured and planned doses were in good agreement. Exceptions occurred mainly at the thyroid (out-of-field) and lenses (extreme sparing). The maximum total dose difference between EPR results and corresponding planned doses was 1.3Gy occurring at the lenses. Remarkably, each LFM and ALA pellet placed within or next to the PTV provided dose values that were within ±4% of the planned dose. Dose deviations from planned dose values were comparable for EPR and TLD measurements. - Conclusion - The results of this proof of principle study suggests that superficial EPR-IVD is applicable in a wide dose range and in various irradiation conditions - being a valuable tool for monitoring cumulative total doses delivered by complex IMRT treatments. EPR-IVD in combination with helical tomotherapy is suitable to reliably detect local dose deviations at superficial dosimeter spots in the order of current national reporting thresholds for significant occurrences (i.e. 10%/4Gy).
Gesehen am 04.10.2022